Chrysoviruses Inhabited Symbiotic Fungi of Lichens - Petrzik, Karel; Koloniuk, Igor; Sehadová, Hana; Sarkisova, Tatiana (Viruses, 2019)
A lichen body is formed most often from green alga cells trapped in a net of ascomycetous fungi and accompanied by endolichenic or parasitic fungi, other algae, and symbiotic or free-living bacteria. The lichen's microcosmos is inhabited by mites, insects, and other animals for which the lichen is a source of food or a place to live. Novel, four-segmented dsRNA viruses were detected in saxicolous Chrysothrixchlorina and Leprariaincana lichens. Comparison of encoded genome proteins revealed classification of the viruses to the genus Alphachrysovirus and a relationship to chrysoviruses from filamentous ascomycetous fungi. We propose the names Chrysothrix chrysovirus 1 (CcCV1) and Lepraria chrysovirus 1 (LiCV1) as acronyms for these viruses. Surprisingly, observation of Chrysothrixchlorina hybridization with fluorescent-labelled virus probe by confocal microscope revealed that the CcCV1 virus is not present in the lichen body-forming fungus but in accompanying endolichenic Penicilliumcitreosulfuratum fungus. These are the first descriptions of mycoviruses from a lichen environment.
Keywords: dvouvláknová RNA; saxicolous lichen; Phylogeny; Fungal Viruses; Viral Proteins; genom virový; genomika; RNA-viry; Lichens; complete genome; symbióza; mykoviry; Symbiosis; chrysovirus; Amino Acid Sequence; virové proteiny; Genome, Viral; RNA Viruses; fylogeneze; lišejníky; RNA, Double-Stranded; ascomycete; confocal microscopy; Genomics; sekvence aminokyselin